The Effect of Width-Mismatch of Modulated Nanowaveguides on the Thermoelectric Efficiency - Antonios-Dimitrios Stefanou; Xanthippi Zianni (Micromachines, 2023)
Width-modulated nanowaveguides are promising for thermoelectric efficiency enhancement because electron and phonon transport properties can be geometrically tuned for improved performance. The shape of the modulation profile drastically affects the transport properties. Optimization of the width modulation for simultaneous maximum thermoelectric transport and minimum thermal transport is challenging because of the interconnected electron and phonon transport properties. We addressed this problem by analysing the effect of each characteristic dimension of a single rectangular modulation unit on electron and phonon transport. We identified distinct behaviours for electrons and phonons. We reveal that whereas phonon thermal conductance decreases with increasing width-mismatch, the electron thermoelectric power factor shows a non-monotonic dependence. It is pointed out that optimal width-mismatch that maximizes thermoelectric efficiency is mainly determined by electron transport and should be identified by maximizing the thermoelectric power. Our work points to a new strategy of optimizing geometry-modulated metamaterials for maximum thermoelectric efficiency.